Small Extracellular Vesicles in Milk Cross the Blood-Brain Barrier in Murine Cerebral Cortex Endothelial Cells and Promote Dendritic Complexity in the Hippocampus and Brain Function in C57BL/6J Mice - Zhou, Fang; Ebea, Pearl; Mutai, Ezra; Wang, Haichuan; Sukreet, Sonal; Navazesh, Shya; Dogan, Haluk; Li, Wenhao; Cui, Juan; Ji, Peng; Ramirez, Denise M. O.; Zempleni, Janos (Frontiers in Nutrition, 2022)
Human milk contains large amounts of exosomes (MEs) and their regulatory microRNA cargos, whereas infant formulas contain only trace amounts of MEs and microRNAs. We assessed the transport of MEs across the blood-brain barrier (BBB) and ME accumulation in distinct regions of the brain in brain endothelial cells and suckling mice. We further assessed BME-dependent gene expression profiles and effects on the dendritic complexity of hippocampal granule cells and phenotypes of BME depletion in neonate, juvenile and adult mice. The transfer of MEs across the BBB was assessed by using bovine fluorophore-MEs labeled in brain endothelial bEnd.3 monolayers and dual chamber systems, and in wild-type newborn pups fostered to exosome and cargo tracking (ECT) dams that express MEs endogenously labeled with a CD63-eGFP fusion protein for subsequent analysis by serial two-photon tomography and staining with anti-eGFP antibodies. Effects of MEs on gene expression and dendritic architecture of granule cells was analyzed in hippocampi from juvenile mice fed exosome and RNA-depleted (ERD) and exosome and RNA-sufficient (ERS) diets by using RNA-sequencing analysis and Golgi-Cox staining followed by integrated neuronal tracing and morphological analysis of neuronal dendrites, respectively. Spatial learning and severity of kainic acid-induced seizures were assessed in mice fed ERD and ERS diets. bEnd.3 cells internalized MEs by using a saturable transport mechanism and secreted miR-34a across the basal membrane. MEs penetrated the entire brain in fostering experiments; major regions of accumulation included the hippocampus, cortex and cerebellum. Two hundred ninety-five genes were differentially expressed in hippocampi from mice fed ERD and ERS diets; high-confidence gene networks included pathways implicated in axon guidance and calcium signaling. Juvenile pups fed the ERD diet had reduced dendritic complexity of dentate granule cells in the hippocampus, scored nine-fold lower in the Barnes maze test of spatial learning and memory (P < 0.01), and the severity of seizures was 5-fold higher following kainic acid administration in adult mice fed the ERD diet compared to mice fed the ERS diet (P < 0.01). MEs cross the BBB and contribute toward optimal neuronal development, spatial learning and memory, and resistance to kainic acid-induced seizures in mice.